Priority Factor Influencing Public Interest In Owning Vehicle With AEB System - Mokhtar, Nur Hazwani; Mohamed Nor, Mohd Khairi; Hamzah, Luqman Hakim; Che Mamat, Ahmad Zul Husni; Abdul Munir, Fudhail (Society of Automotive Engineers Malaysia., 2019)
The Autonomous Emergency Brake (AEB) is a part of autonomous vehicle technologies and the technology was developed to reduce human errors that lead to a road accident. This survey investigates the priority factor influencing the public in acquiring vehicles with the AEB system. In this study, the Analytic Hierarchy Process (AHP) framework was used to determine the public’s rating of importance of the availability of the AEB system in their vehicles. Cronbach’s alpha was used to check for reliability of survey items. With a score of 0.8, it suggested that the items had relatively high internal consistency. The results show that the top factors that influence public interest in having vehicle with AEB are the reduction of the severity of injury and crashes.